GLOBAL GOLD PRICE VOLATILITY AND ITS CORRELATION TO RESOURCE AND RESERVE DYNAMICS AT PT MERDEKA COPPER GOLD TBK - Utari Retno Sulistyo Rini; Fanteri Aji Dharma Suparno; Siti Aminah; Haeruddin (Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2025)
Gold (Au) commonly occurs as nuggets or grains in rock veins and alluvial deposits. Because of its scarcity, chemical stability, and distinctive properties, gold commands higher market prices than base metals. Global gold price volatility has a significant impact on the strategic decisions of mining companies. This study aims to quantify the correlation between international gold price fluctuations and the dynamics of gold resources and reserves at PT Merdeka Copper Gold Tbk. Using a quantitative approach, the average gold prices and the company's annually reported resource and reserve figures were analyzed. The Pearson correlation coefficient was employed to measure the strength and direction of the relationship. The results reveal a robust and statistically significant negative correlation. This inverse relationship suggests that periods of high price volatility are associated with a decrease in the company's reported gold resources and reserves. The findings highlight the significant impact of external market dynamics on resource management. It is recommended that stakeholders incorporate market volatility forecasts into long-term strategic planning and resource valuation models to enhance resilience.